Financial Crises, Financial Dependence, and Industry Growth - Laeven, Luc; Klingebiel, Daniela; Kroszner, Randy (World Bank, Washington, D.C., 2013)
The authors investigate the link between financial crises and industry growth. They analyze data from 19 industrial and developing countries that have experienced financial crises during the past 30 years to investigate how financial crises affect sectors dependent on external sources of finance. Specifically, the authors examine whether the impact of a financial crisis on externally dependent sectors varies with the depth of the financial system. They find that sectors highly dependent on external finance tend to experience a greater contraction of value added during a crisis in deeper financial systems than in countries with shallower financial systems. They hypothesize that the deepening of the financial system allows sectors dependent on external finance to obtain relatively more external funding in normal periods, so a crisis in such countries would have a disproportionately negative effect on externally dependent sectors. In contrast, since externally dependent firms tend to obtain relatively less external financing in shallower financial systems (and hence have relatively lower growth rates in such countries during normal times), a crisis in such countries has less of a disproportionately negative effect on the growth of externally dependent sectors.